ANALISIS KEBUTUHAN PENDIDIKAN KESEHATAN REPRODUKSI PADA SISWA SMP DI WILAYAH KECAMATAN PEDURUNGAN SEMARANG - Indira Krisma Rusady; Zahroh Shaluhiyah; Besar Tirto Husodo (Jurnal Kesehatan Masyarakat (Undip), 2017)
The incidence of pregnancy outside marriage among adolescents aged junior high school in Semarang from 2014 until June 2016 have continued to rise. Low education of reproductive health is one of the reason. Reproductive health education in 6 schools has not been going according to the needs of the students. This research aims to analyze the needs of reproductive health education in Junior High School students at Pedurungan Semarang.This research uses a quantitative with cross sectional approach. The populations are 6 junior high school in Pedurungan with multistage sampling technique was obtained 100 samples. This research use univariate and bivariat.The research showed that more than half of the respondents are female (55%), 12-14 years old (82%), most menarche age is 12 years old (30%) and most wet dream age is 13 years old (20%). More than half of the respondents (53%) require reproductive health education, the material of interest is puberty, how to care for reproductive organs and healthy courtship provided through video media and or artificial bodies followed by discussion and or role play are provided by health workers. The chi-square test showed that sexual behavior (p=0,001), access to pornographic media (p=0,010) and locus of control (p=0,000) are related to reproductive health education needs. While the variables of age (p=0,287), knowledge (p=0,724), attitude (p=1,000), religiosity (p=0,229) and self esteem (p=0,052) are not related to reproductive health education needs.It is advisable to provide material about puberty are done in a comprehensive manner through the medium of the video continued with the discussion that given by health workers, support school infrastructure and optimize the role of health workers.